The Duty to Rescue and Randomized Controlled Trials Involving Serious Diseases - Millum, Joseph (Journal of moral philosophy, 2018)
During the recent Ebola epidemic, some commentators and stakeholders argued that it would be unethical to carry out a study that withheld a potential treatment from affected individuals with such a serious, untreatable disease. As a result, the initial trials of experimental treatments did not have control arms, despite important scientific reasons for their inclusion. In this paper, we consider whether the duty to rescue entails that it would be unethical to withhold an experimental treatment from patient-participants with serious diseases for which there are no effective treatments, even when doing so is scientifically necessary to test the effectiveness of the treatment. We argue that the duty to rescue will rarely apply. The context of medical research also throws new light on the content of the duty to rescue, since the interests of future patients—who stand to benefit from the fruits of medical research—are relevant to whether the duty applies.